Depth profiling with SNMS and SIMS of Zn(O, S) buffer layers for Cu(In, Ga)Se2 thin‐film solar cells. (30th September 2013) - Eicke, Axel; Ciba, Thomas; Hariskos, Dimitrios; Menner, Richard; Tschamber, Carsten; Witte, Wolfram
Abstract : Zn(O, S) is a promising candidate to replace the commonly used CdS buffer layer for Cu(In, Ga)Se2 (CIGS) thin‐film solar cells due to its non‐toxicity and its potential to enhance the conversion efficiency of the CIGS solar cell. The composition of chemical bath deposited (CBD) and sputtered Zn(O, S) layers with thicknesses well below 100 nm was determined by sputtered neutral and secondary ion mass spectrometry (SNMS and SIMS). Despite numerous mass interferences of double‐charged atoms and dimers with single Zn, O and S isotopes, we developed an evaluation algorithm for quantification of SNMS depth profiles of Zn(O, S) layers. In particular, the superposition of double‐charged S and Zn atoms with O and S isotopes is accounted for numerically in the quantification procedure. For sputtered Zn(O, S) layers, the S/(S + O) atomic ratio and the vertical composition profile can be controlled by the O2 content in the gas flow and the substrate temperature during sputtering whereas for CBD Zn(O, S) the S/(S + O) ratio is constant around 0.7–0.8. A Cu‐depleted layer of about 5 nm on the CIGS surface after buffer deposition was observed for both preparation methods. With negative SIMS, we found more hydroxides and carbon residues in CBD Zn(O, S) as compared to sputtered layers. Best cell performance with sputtered Zn(O, S) layers was achieved for S/(S + O) ratios of 0.25–0.40, yielding efficiencies up to 13%. Our solar cells with CBD Zn(O, S) buffers exhibit higher efficiencies due to an improved open‐circuit voltage. Copyright © 2013 John Wiley & Sons, Ltd.